Predisposing Factors and Outcome of Preterm Birth in a Tertiary Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Preterm birth is a challenging issue for both mother and baby, and pose major threat to newborn survival. The purpose of this study was to find out the magnitude of preterm birth, factors predisposing to preterm birth and its outcome during perinatal period. This was a cross sectional study, conducted among mothers admitted with a gestational age > 28 weeks to < 37 weeks in Obstetrics and Gynae department of Institute of Child and Maternal Health (ICMH). During March-June, 2013, data was collected through face to face interview using structured questionnaire and review of hospital records. Data analysis done using SPSS version 20. Among enrolled 103 women mean age was 23.3±4 years, 64% were multigravida, about 78% were late preterm (35-37 weeks). Commonest associated factor was premature rupture of membrane (53.7%). Other factors were Preeclampsia (16%), UTI (12%) and moderate anaemia (75%). Neutrophilia was found in 7.6%, urinary pus cell raised in 37% and vaginal infection was found in 7.6%. Corticosteroids was given for lung maturity to 55% and Tocolytics used in 11 % mothers. About 50% born by CS, 24% by Obstetric Forceps and 26% by spontaneous vaginal delivery. Puerperal Pyrexia was the most common postpartum complication. Delayed cry was in 66%, , 56% required admission to neonatal ward, of them 91% and 45% belong to gestation age 28-34 weeks and 35-37 weeks respectively. Perinatal death was in 2%, 24.3% had neonatal jaundice and 29 % developed septicemia Preterm birth is associated with several risk factors like paternal smoking, high parity, infection and premature rupture of membrane. Change in obstetric practices in favor of early termination by caesarean section for maternal or fetal indication is also an important determining factor for preterm birth. Awareness among health professionals and public should be made for avoidance of risk factors and adoption of risk specific strategies may contribute to reduction of preterm births and its complications.Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 74-80